Superbubble Feedback in RAMSES - Gallant, Dennis (My University, 2020)
We present a new model for stellar feedback in the hydrodynamics code RAMSES. This model, called the superbubble model, represents many temporally and spatially-clustered supernova events combining to form a single large bubble. It avoids the overcooling problem by splitting the gas into two distinct phases with their own temperatures and densities. It features conduction and a sub-grid implementation of evaporation in order to facilitate mass-loading of the bubble's interior. We find that this model produces bubbles 40% larger, and preserves four times as much of the supernovae energy, compared to the default RAMSES case. These results are similar to those obtained in earlier work in the Gasoline code by Keller et al (2014), and demonstrate that the superbubble model is an effective way of generating the feedback necessary to simulate galaxies without relying on any free parameters or ad hoc adjustments.
Keywords: Astrophysics; Simulation; Galaxies; Feedback